The ACE-2 in COVID-19: Foe or Friend? - Dalan, Rinkoo; Bornstein, Stefan R.; El-Armouche, Ali; Rodionov, Roman N; Markov, Alexander; Wielockx, Ben; Beuschlein, Felix; Boehm, Bernhard O. (Hormone and Metabolic Research, 2020)
COVID-19 is a rapidly spreading outbreak globally. Emerging evidence demonstrates that older individuals and people with underlying metabolic conditions of diabetes mellitus, hypertension, and hyperlipidemia are at higher risk of morbidity and mortality. The SARS-CoV-2 infects humans through the angiotensin converting enzyme (ACE-2) receptor. The ACE-2 receptor is a part of the dual system renin-angiotensin-system (RAS) consisting of ACE-Ang-II-AT1R axis and ACE-2-Ang-(1–7)-Mas axis. In metabolic disorders and with increased age, it is known that there is an upregulation of ACE-Ang-II-AT1R axis with a downregulation of ACE-2-Ang-(1–7)-Mas axis. The activated ACE-Ang-II-AT1R axis leads to pro-inflammatory and pro-fibrotic effects in respiratory system, vascular dysfunction, myocardial fibrosis, nephropathy, and insulin secretory defects with increased insulin resistance. On the other hand, the ACE-2-Ang-(1–7)-Mas axis has anti-inflammatory and antifibrotic effects on the respiratory system and anti-inflammatory, antioxidative stress, and protective effects on vascular function, protects against myocardial fibrosis, nephropathy, pancreatitis, and insulin resistance. In effect, the balance between these two axes may determine the prognosis. The already strained ACE-2-Ang-(1–7)-Mas in metabolic disorders is further stressed due to the use of the ACE-2 by the virus for entry, which affects the prognosis in terms of respiratory compromise. Further evidence needs to be gathered on whether modulation of the renin angiotensin system would be advantageous due to upregulation of Mas activation or harmful due to the concomitant ACE-2 receptor upregulation in the acute management of COVID-19.
Keywords: COVID-19; ACE-2; renin angiotensin system